FAHR'S Sy ndrome: A rare Neurodegenerative Disorder - Ahad, Md Abdul; Kamal, SM; Salma, Umme (Medicine Today, 2017)
Idiopathic Basal Ganglia Calcification, also known as Fahr disease or Fahr's Syndrome or Bilateral StriatoPallidoDentate Calcinosis (BSPDC) is a rare, genetically dominant, inherited neurological disorder characterized by abnormal deposits of calcium in areas of the brain that control movement, including the basal ganglia and the cerebral cortex. A rare idiopathic disease which manifests in middle age characterized by punctate areas of non-arteriosclerotic calcination in parts of the gray and dentate nuclei, particularly of smaller brain vessels. The symptoms include mental and growth retardation, dystonic movements, and athetosis. May be caused by a malfunction of the glandula parathyreoidea. The term Fahr triad consists of symmetrical calcification of the basal ganglia, neuropsychiatric symptoms, and hypofunction of the parathyroid gland. Treatment is directed toward minimizing symptoms. The prognosis for any individual with Fahr's Syndrome is variable and hard to predict. Progressive neurological deterioration generally results in disability and death. Medicine Today 2017 Vol.29(1): 39-41